Analysis and Characterization of PEMFC Power Systems with Bond Graph - Nedjem Eddine Benchouia; Elias Hadjadj Aoual; Lakhdar Khochemane; Bouziane.Mahmah (My University, 2013)
This paper addresses the problem of bond graph methodology as a graphical approach for modeling fuel cell systems. The system consists of a Proton Exchange Membrane Fuel Cell (PEMFC) stack and an interleaved boost converter. Simulation results illustrate the simplified system response obtained using the implementation of the governing equations in MATLAB/Simulink or a bond graph